2014
DOI: 10.3390/md12125930
|View full text |Cite
|
Sign up to set email alerts
|

Sargassopenillines A–G, 6,6-Spiroketals from the Alga-Derived Fungi Penicillium thomii and Penicillium lividum

Abstract: Seven new 6,6-spiroketals, sargassopenillines A–G (1–7) were isolated from the alga-derived fungi Penicillium thomii KMM 4645 and Penicillium lividum KMM 4663. The structures of these metabolites were determined by HR-MS and 1D and 2D NMR. The absolute configurations of compounds 1, 5 and 6 were assigned by the modified Mosher’s method and by CD data. Sargassopenilline C (3) inhibited the transcriptional activity of the oncogenic nuclear factor AP-1 with an IC50 value of 15 µM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 21 publications
(26 reference statements)
0
18
0
1
Order By: Relevance
“…Similar anti-inflammatory effects were also evidenced in murine peritoneal macrophages for novel ester derivatives of hexylitaconic acid [ 115 ], and for penicillinolide A [ 138 ] ( Figure 2 ). Weak NF-κB inhibitory properties were again reported from penilactone A [ 125 ], while sargassopenilline C has been found to inhibit the transcriptional activity of AP-1 [ 160 ] ( Figure 2 ). Finally, and again in BV2 cells, 2E , 4Z -tanzawaic acid D was found to inhibit the production of iNOS [ 158 ].…”
Section: Bioactivities Of Novel Compoundsmentioning
confidence: 97%
See 1 more Smart Citation
“…Similar anti-inflammatory effects were also evidenced in murine peritoneal macrophages for novel ester derivatives of hexylitaconic acid [ 115 ], and for penicillinolide A [ 138 ] ( Figure 2 ). Weak NF-κB inhibitory properties were again reported from penilactone A [ 125 ], while sargassopenilline C has been found to inhibit the transcriptional activity of AP-1 [ 160 ] ( Figure 2 ). Finally, and again in BV2 cells, 2E , 4Z -tanzawaic acid D was found to inhibit the production of iNOS [ 158 ].…”
Section: Bioactivities Of Novel Compoundsmentioning
confidence: 97%
“…Radical scavenging effects were also reported for compound JBIR-59 ( Figure 3 ), on account of its protective effects against l -glutamate toxicity in neuronal hybridoma N18-RE-105 cells [ 99 ]. A few more products ( Figure 3 ) have been characterized as free radical scavengers based on their activity against 1,1-diphenyl-2-picrylhydrazyl (DPPH), such as the terrestrols [ 64 ], 4,6,4′,6′-tetrabromo-3,3′-dihydroxy-5,5′-dimethyldiphenyl ether and 4,6,2′,4′,6′-pentabromo-3,3′-dihydroxy-5,5′-dimethyldiphenyl ether [ 105 ], the variecolorins [ 102 ], compound JBIR-124 [ 100 ], and sargassopenillines A and E [ 160 ]. Further indirect antitumor effects resulting from detoxification of xenobiotics have been proposed for the meroterpenoid penicillipyrone B ( Figure 3 ) for its ability to induce the enzyme quinone-reductase, which is involved in the reduction of electrophilic quinones [ 151 ].…”
Section: Bioactivities Of Novel Compoundsmentioning
confidence: 99%
“…179,[253][254][255][256][257][258] The genus Penicillium was the source of many other metabolites 400-461. [259][260][261][262][263][264][265][266][267][268][269][270][271][272][273][274][275][276][277][278] Other genera to yield new the metabolites 462-520 were Pseudallescheria, Spicaria, Spiromastix, Stachybotrys, Talaromyces, Trichoderma, Xylaria and Xylariaceae, [279][280][281][282][283][284][285][286][287][288][289][290][291] while 521 was obtained from a strain of the order Xylariales and also synthesised. 292 A number of syntheses of fungal metabolites have resulted in structural revisions of the natural products, including syntheses of (À)-protubonine A 522, (À)-protubonine B 523 (Aspergillus sp.)…”
Section: Marine-sourced Fungi (Excluding From Mangroves)mentioning
confidence: 99%
“…Secondary metabolites obtained from algal-derived fungi, which possess unique structures and interesting biological properties, have attracted considerable attention in recent years [1][2][3]. As part of our continuing efforts to discover novel metabolites in fungi we have previously identified seven new 6,6-spiroketals,sargassopenillines A−G [4], from the fungi Penicillium thomii KMM 4645 and P. lividum KMM 4663 isolated from the marine brown alga Sargassum miyabei. Further investigation of the metabolites of the fungal strain P. lividum KMM 4663 has now led to the isolation of a new 6,6-spiroketal,sargassopenilline H (1), and the known peneciraistin C (2) ( Figure 1).…”
mentioning
confidence: 99%
“…These data and NOE correlations between H 3 -15 with H-5b and between H-5a with H 3 -16 and H-6 ( Figure 2) indicated that the CH 3 -15, 6-OH and H-5b are on the same face of the bicyclic isochromene core and H-5a and CH 3 -16 are on the other side. Thus the absolute configurations of C-6 and C-4 were assigned as S. The NOE correlation H-12/ H-1b ( H 4.09) indicated a β-orientation for the 14-methyl group and suggested the configuration of C-3 was S [4,6,7]. The small coupling constants of the H-9 signal at δ 4.81 (1H, t, 2.8) and biogenetic relationship between sargassopenilline A [4] and 1 suggested an α-orientation for the 9-acetoxy group.…”
mentioning
confidence: 99%